Optimization of the Role of the Corruption Eradication Commission in the Efforts of Corruption Prevention and Eradication - Bunga A. S. Abadiyah; Veithzal Rivai Zainal; Aziz Hakim (Journal of Law, Politic and Humanities, 2025)
Corruption is a major problem that hinders Indonesia's progress, undermines government systems, and deteriorates public services. The Corruption Eradication Commission (KPK) plays an important role in preventing and combating corruption. However, the KPK's success is still hindered by a number of problems, including political resistance, lack of resources, and regulatory weaknesses. The purpose of this study is to evaluate the efforts made by the KPK to maximize their role in preventing and combating corruption by focusing on the elements of education, prosecution, coordination, and regulatory strengthening. A descriptive analysis of KPK's policies, programs, and implementation was used in this study. The results show that KPK's education programs are effective in raising public awareness, but changes are needed to reach more people. Challenges such as legal barriers and political pressure continue to exist in the field of prosecution, although major cases have been resolved successfully. Inter-agency coordination has been assessed, but strengthening is needed to become more synergistic. Conversely, anti-corruption laws should be amended to correct legal weaknesses that are often used by corrupt actors. To ensure sustainable corruption eradication in Indonesia, this study suggests enhancing KPK's institutional capacity, innovation in education programs, inter-agency policy harmonization, and regulatory revisions.